Bioenergetics of sulfur reduction in the hyperthermophilic archaeon Pyrococcus furiosus. - Schicho, R N (1993)
The bioenergetic role of the reduction of elemental sulfur (S0) in the hyperthermophilic archaeon (formerly archaebacterium) Pyrococcus furiosus was investigated with chemostat cultures with maltose as the limiting carbon source. The maximal yield coefficient was 99.8 g (dry weight) of cells (cdw) per mol of maltose in the presence of S0 but only 51.3 g (cdw) per mol of maltose if S0 was omitted. However, the corresponding maintenance coefficients were not found to be significantly different. The primary fermentation products detected were H2, CO2, and acetate, together with H2S, when S0 was also added to the growth medium. If H2S was summed with H2 to represent total reducing equivalents released during fermentation, the presence of S0 had no significant effect on the pattern of fermentation products. In addition, the presence of S0 did not significantly affect the specific activities in cell extracts of hydrogenase, sulfur reductase, alpha-glucosidase, or protease. These results suggest either that S0 reduction is an energy-conserving reaction, i.e., S0 respiration, or that S0 has a stimulatory effect on or helps overcome a process that is yield limiting. A modification of the Entner-Doudoroff glycolytic pathway has been proposed as the primary route of glucose catabolism in P. furiosus (S. Mukund and M. W. W. Adams, J. Biol. Chem. 266:14208-14216, 1991). Operation of this pathway should yield 4 mol of ATP per mol of maltose oxidized, from which one can calculate a value of 12.9 g (cdw) per mol of ATP for non-S0 growth. Comparison of this value to the yield data for growth in the presence of S0 reduction is equivalent to an ATP yield of 0.5 mol of ATP per mol of S0 reduced. Possible mechanism to account for this apparent energy conservation are discussed.